Indoor nitrogen dioxide in homes along trunk roads with heavy traffic. Issue 6 (June 1998) - Shima, M; Adachi, M
Abstract : OBJECTIVES: To assess the distribution of indoor nitrogen dioxide (NO2) concentrations in homes located in differing environments, and to investigate the influence of factors such as automobile exhaust on the indoor environment. METHODS: The concentrations of indoor NO2 over 24 hours were measured in both the heating and non-heating periods in homes of pupils from nine elementary schools in Chiba, Japan. Information on factors that could influence indoor environments was collected by questionnaire. RESULTS: Indoor NO2 concentrations during the heating period were higher in homes with unvented heaters than in homes with vented heaters, although the concentrations varied greatly among homes primarily because of the type of heating device used. During the non-heating period, indoor NO2 concentrations were significantly higher in homes adjacent to trunk roads than in homes located in other areas. Multiple regression analysis showed that indoor NO2 concentrations were associated with atmospheric NO2 in homes with vented heaters during the heating period, and in homes in areas other than on the roadside during the non-heating period. In areas other than the roadside, cigarette smoking in indoor environments also significantly contributed to indoor NO2. The average concentrations of indoor NO2 in the homes of pupils attending each school were significantly related to the atmospheric NO2 in areas other than the roadside. However, the relation between indoor and atmospheric NO2 concentrations was not significant in roadside areas. CONCLUSIONS: These findings suggest that indoor NO2 concentrations are related to the atmospheric NO2 and type of heating appliances, and are also affected by automobile exhaust in homes located in roadside areas.